Reading the Post-Apartheid City - Moreillon, Olivier (Logos Verlag Berlin, 2019)
This study analyses the representation of Durbanite and Capetonian urban spaces in the following selection of post-apartheid works: Mariam Akabor's ''Flat 9'', Rozena Maart's ''Rosa's District Six'', Johan van Wyk's ''Man Bitch'', K. Sello Duiker's ''Thirteen Cents'', Bridget McNulty's ''Strange Nervous Laughter'', and Lauren Beukes' ''Moxyland''. The focus lies on the interrelatedness of shifting post-apartheid subjectivities and urban space (and place) in these literary works. The analysis not only grants access to different 'new voices` of post-apartheid literature, it also sheds light on the perception of South African history, urban geography, and cultural topography - essentially, on real as well as imagined South African urban spaces - as the literary representations of city-spaces become archives of cultural transformation processes; a gateway to the understanding of the developments and changes of, and within, the two cities in question.